Therapeutic Efficacy of Liquid Nitrogen Cryotherapy for Treatment of Alopecia Areata - Samia Aslam, Tuyiba Ilyas, Shaanfa Kaleem, Saadia Ilyas, Zaira Aslam, Attia Tabassum (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To assess the therapeutic efficacy of liquid nitrogen cryotherapy for treatment of alopecia areata. Study Design: Descriptive Case Series. Place and Duration of Study: Department of Dermatology at Mayo Hospital, Lahore from 15-10-2020 to 14-04-2021. Methodology: A total of 95 patients were included in the study. A photograph was obtained at baseline. Then, patients were treated with superficial liquid nitrogen cryotherapy spray once weekly for 6 weeks. A cryogun was used to spray the lesion with liquid nitrogen for 2–3 s till the appearance of mild frost. After the frozen area was thawed (3–5 s), a second spray was done in the same manner. After 6 weeks, session was stopped and patients were followed-up at 3 months and 6 months. Results: Patients ranged between 16-70 years of age with mean age of 29.5±11.9 years. Out of 95 patients, 43 (45.3%) were male while 52 (54.7%) were female. Mean duration of disease was 9.8±4.9 months. Therapeutic efficacy of liquid nitrogen cryotherapy was found to be significant in 26 patients (27.4%). Stratification for age, gender and duration of disease was carried and no association was found (p >0.05). Conclusion: In conclusion cryotherapy with liquid nitrogen is a therapeutic option with a good treatment outcome. It has the privilege of being a simple, convenient, short-term, and office-based technique. Key Words: Alopecia Areata, Liquid Nitrogen Cryotherapy, Treatment.